Prototype Atap Cerdas Dengan Multisensor Berbasis Internet of Thing (IoT) - Usman Maulana Riyansyah; Yan Mitha Djaksana (CV. Multi Kreasi Media, 2022)
The roof is a medium for covering the house from various weathers, both hot and rainy. Usually, the roof is used to protect goods or clothes from the rain that suddenly comes. Most people to dry clothes or food requires sufficient sunlight to dry it. However, sometimes the weather is difficult to predict because of the sudden arrival of rain which results in no time for someone to secure their clothesline. The purpose of this research is to make it easier for users to secure their clotheslines so they are not exposed to rain water in order to save time when closing the roof. This research method uses fuzzy logic and nodemcu esp8266 which is connected to a smartphone connected via the internet so that the roof is controlled automatically or manually. Based on the results of the research, the smart roof tool can be controlled with the maximum distance that can be reached by wifi to connect to a smartphone is 10 meters, and the minimum distance that can be reached is 1 meter. wifi can be connected horizontally or vertically as long as it is within the signal radius. The conclusion of the study is that a smart roof system with internet-based multisensory things is as a security to avoid the rainy weather that suddenly comes and also makes it easier for drying so that it is not easily exposed to rain, or too hot when feeling the weather at that time.